Analisis Konsep Matematika Materi Bilangan Dalam Al-Qur’an - Surani, Nur Eka; Wahyuni, Indah (Program Studi Sarjana Pendidikan Matematika, Universitas Singaperbangsa Karawang, 2023)
The research problem is focused on the mathematical concept of number material contained in the Qur'an. The purpose of the research is to find out the mathematical concept of number material in the Qur'an is true. This research was conducted using the Library Research method. The results of the research are arranged in a narrative based on the study process of various sources in journals, books and other sources, which are in accordance with the issues discussed. Indeed, there are many studies contained in the Qur'an that explain the concept of mathematics. Therefore, to study the Qauniyyah verses in the Qur'an, mathematics is needed. Thus mathematics is also able to provide an approach in understanding the verses of Qauniyyah because mathematics is a science that plays an important role in education, sometimes referred to as the